Rational modes determination of traction motors loading-back for electric rolling stock in mainline and industrial transport - Afanasov, A. M. (Science and Transport Progress, 2014)
Purpose. Loading-back systems are used for post-maintenance acceptance tests of electric traction motors of electric rolling stock (ERS) in mainline and industrial transport. The aim of the research is justification of choice method of the rational loading-back parameters of traction electric motors during the tests for heating. Methodology. At the heart of the choice method justification of the rational loading-back parameters is a theory of heating the homogeneous solid body and well-known methods of heating calculations of traction electric machines. Findings. Expediency of heating tests for electric traction motors at load currents equal to the starting current (for ERS of mainline transport) or fifteen minutes current (for ERS of industrial transport) was substantiated. It was shown that this increase of load current will reduce the electricity costs of the tests for 20–30% and shorten the tests duration for three–four times while ensuring the corrected power minimum of energy sources in loading-back system. Originality. It is shown that the energy costs for heating tests of the traction motors can be reduced by both the increasing the energy efficiency of the loading-back system and by the optimizing of loading mode of traction electric machines. Choice technique of rational modes of loading-back for electric traction motors of rolling stock in mainline and industrial transport was grounded. Practical value. Load current increase of traction electric motors during their tests for heating will reduce the total electricity consumption for the acceptance tests, reduce test time and total material costs for repair of the electric traction motors of rolling stock in mainline and industrial transport.